1991
DOI: 10.1128/aac.35.11.2191
|View full text |Cite
|
Sign up to set email alerts
|

Ganciclovir-resistant cytomegalovirus clinical isolates: mode of resistance to ganciclovir

Abstract: Cytomegalovirus strains with reduced in vitro susceptibilities to ganciclovir have been recovered from patients who failed long-term ganciclovir therapy. The ganciclovir-resistant clinical isolates in this study were unable to induce ganciclovir phosphorylation in virus-infected cells. The viral DNA polymerase function appeared unaltered in one genetically pure ganciclovir-resistant strain, compared with that of its wild-type ganciclovir-sensitive counterpart. All nine of the ganciclovir-resistant strains were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(84 citation statements)
references
References 43 publications
2
82
0
Order By: Relevance
“…Sequential plasma samples were separated from the same heparinized blood specimens obtained for culture. 10 epidemiologically unrelated patients (patients [1][2][3][4][5][6][7][8][9][10] were selected on the basis of clinical resistance to ganciclovir therapy. The patients received an initial induction course of intravenous ganciclovir (5 mg/kg twice daily) followed by maintenance therapy of intravenous ganciclovir (5 mg/kg daily).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequential plasma samples were separated from the same heparinized blood specimens obtained for culture. 10 epidemiologically unrelated patients (patients [1][2][3][4][5][6][7][8][9][10] were selected on the basis of clinical resistance to ganciclovir therapy. The patients received an initial induction course of intravenous ganciclovir (5 mg/kg twice daily) followed by maintenance therapy of intravenous ganciclovir (5 mg/kg daily).…”
Section: Methodsmentioning
confidence: 99%
“…of in vitro resistant strains ( 1,2). Resistance in clinical isolates has been phenotypically associated with impaired ganciclovir phosphorylation in infected cells (3). However, the genotypic basis for clinical ganciclovir resistance has not been resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The 50% effective concentration (EC so) of C.OXT-G against HCMV has been shown to be comparable to that of GCV against HSV (21,36), despite its lower level of phosphorylation in the HCMV-infected cells (36). The finding that the triphosphate form of C.OXT-G is a potent competitive inhibitor of HCMV polymerase with a 2-log-more potent Ki than that of triphosphorylated GCV (33,36), suggested that the antiviral potency of C.OXTs is based on their ability to inhibit viral DNA polymerases.…”
mentioning
confidence: 99%
“…Furthermore, cidofovir is effective against the majority of GCV resistant clinical isolates (those resulting from a defect in the protein coded for by UL97) (Stanat et et., 1991), as well as PFA resistant viruses generated in vitro (Snoeck et el., 1995) and in vivo (unpublished observations) as a result of PFA treatment alone. Since HCMV disease primarily occurs in two populations of patients (AIDS and organ transplant) who often receive multiple drugs for the treatment of more than one disease, it is critical to investigate the possible synergistic/antagonistic interactions that may occur between drug combinations.…”
Section: Introductionmentioning
confidence: 99%